Military Propaganda and Disinformation: How Issah Mobila's Murder was Spun in the Media - Mahama, Seth Sayibu (Journal of Communication, 2023)
Purpose: The study investigates the use of propaganda in the media by Ghana's military in the media coverage of the murder of Issah Mobila in military custody in Ghana's northern town of Tamale. Mobila was murdered in 2004 by the military after his arrest by the civil police with an allegation of possession of arms that he intended to use to cause post-election violence in Tamale. Even though the military earlier denied the murder, an autopsy report confirmed that the deceased was murdered in military custody. A military inquiry report indicted some seven soldiers, two of whom were later jailed by a Fast Track High Court in Accra. Methodology: The study employed qualitative research design to generate data through interviews. Internet sources and published works on military brutalities of civilians in Africa were also used. Local media coverage of the event was extensive and radio phone-in programmes witnessed condemnation and anger from the people regarding the manner Mobila was tortured and killed in military custody. Findings: The study found that the military command in Tamale deployed propaganda techniques in order to evade responsibility for the death of Mobila in its custody. It also found that local media coverage of the event was biased and did not conform with the tenets of objectivity. Unique Contribution to Theory, Policy and Practice: The study which is the first on propaganda and military murder of a civilian in military custody in Ghana recommended the training of journalists in detecting propaganda frames in reporting so as to obviate biased reportage in conflict situations.